Are serological tests of value in diagnosing and monitoring response to treatment of syphilis in patients infected with human immunodeficiency virus?. Issue 4 (August 1988) - Terry, P M; Page, M L; Goldmeier, D
Abstract : To assess the value of serological tests in diagnosing and monitoring the response to treatment of syphilis in patients infected with the human immunodeficiency virus (HIV), case notes of eight homosexual men with a history of treated syphilis, positive reactions to serological tests for syphilis, and documented subsequent conversion to HIV seropositivity were studied. No change was noted in serological markers of syphilis after HIV infection. The case notes of one man with primary syphilis, four men with secondary syphilis, and three men with latent syphilis, of whom all were HIV seropositive, were also studied. In seven of these patients the serological responses to infection and after treatment were consistent with the experience of syphilis in HIV seronegative patients. In one man treated for secondary syphilis, and confirmed as HIV seropositive eight months after treatment, the rapid plasma reagin (RPR) test result continued to be positive at a high titre for up to 20 months after treatment.